2019
DOI: 10.2174/1573403x15666181205110624
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Atrial Fibrillation: A Review of Epidemiology, Management, and Outcomes

Abstract: Atrial fibrillation is the most common sustained cardiac arrhythmia. The scope and impact of atrial fibrillation are wide; it can affect cardiac function, functional status, and quality of life, and it confers a stroke risk. There are sex differences in atrial fibrillation across the scope of the disease process, from epidemiology and causative mechanisms to management and outcomes. The approach to management of atrial fibrillation differs between women and men, and there are sex differences in response to med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 81 publications
5
116
0
22
Order By: Relevance
“…Furthermore, research has shown a direct effect of sex hormones on ion channels and their expression, with implications for arrhythmogenesis and clinical outcome in AF [ 83 ]. Evidence also reveals gender-specific outcomes of antiarrhythmic drugs and catheter ablation, with more adverse effects in women than in men [ 84 ].…”
Section: Gender Aspects Of Coping With Afmentioning
confidence: 99%
“…Furthermore, research has shown a direct effect of sex hormones on ion channels and their expression, with implications for arrhythmogenesis and clinical outcome in AF [ 83 ]. Evidence also reveals gender-specific outcomes of antiarrhythmic drugs and catheter ablation, with more adverse effects in women than in men [ 84 ].…”
Section: Gender Aspects Of Coping With Afmentioning
confidence: 99%
“…[1][2][3][4] Most studies suggest that women have higher rates of AF recurrence after ablation and in general, lower rates of procedural "success" (variably defined). [1][2][3] Several potential mechanisms have been offered for lower procedural efficacy in women including delayed referral for ablation, a higher prevalence of comorbidities, and more advanced AF substrate at the time of ablation, including a higher prevalence of non-pulmonary vein triggers. 2,3,5,6 Importantly, studies also suggest that women experience a higher rate of complications related to AFCA, in particular vascular complications and bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several potential mechanisms have been offered for lower procedural efficacy in women including delayed referral for ablation, a higher prevalence of comorbidities, and more advanced AF substrate at the time of ablation, including a higher prevalence of non-pulmonary vein triggers. 2,3,5,6 Importantly, studies also suggest that women experience a higher rate of complications related to AFCA, in particular vascular complications and bleeding. 2,4,6,7 However, most studies which have assessed complication rates based on sex have been underpowered to look at less commonly occurring complications, such as stroke and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…We found that gender may be an important factor affecting the failure of atrial fibrillation in such patients, male (OR 0.192 ,95% CI 0.029-1.279, p 0.088). It seems that men have a higher cardioversion success rate than women, and many catheter radiofrequency ablation procedures have reported similar results [16,17] . Pate and lee ' s study found that the high rate of female radiofrequency ablation regurgitation failure may be associated with higher BMI in women, more ectopic pacing points (non-pv trigers), and higher parasympathetic tension [18,19] .…”
Section: Discussionmentioning
confidence: 99%